Effectiveness of a Planning Support System Targeting Rebuilding in Immersive Virtual Environment in Fukui, Japan - Yuya, Yamato; Taisei, Osada; Tutuko, Pindo; Dinh-Thanh, Nguyen; Aini, Nurul (University of Merdeka Malang, 2024)
Resident participation is an essential part of community development. In order to reflect residents' opinions, it is considered necessary to conduct workshop. We apply the community development guidance method (hereinafter, CDGM). The CDGM is a method that allows the replacement or deregulation of some of the regulations of the Building Standard Law by the agreement of the residents of a certain area. However, it takes a deal of time and effort to build consensus among residents, and the CDGM is to obtain their consensus. Therefore, this study is to examine effectiveness of an immersive planning support system for architectural rebuilding using virtual space and the CDGM. We believe that an immersive planning support system in a virtual environment is effective because it allows residents to enter and experience the street after the plan has been updated, making it easier for them to imagine the street. As a result, we confirmed the applicability of this technology to community briefings.